Quantifying the training demands of an amateur women's Rugby union team using Global Positioning System - Mbane, Nomabhelu (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Rugby union is a dynamic sport that has grown to not only be played by men but by women too. The professionalisation of the sport that happened in 1995 developed the game immeasurably including the focus given to its scientific research. This is important as literature on the demands of the game has become vital in improving the performance of Rugby union players (Deutch et al., 1998; Kay and Gill, 2004; Kruger, 2012). Scientific evidence-based data on the physical and physiological demands is imperative in the planning and setting up of training regimes (Deutch et al., 1998; Kay and Gill, 2004; Kruger, 2012). Unfortunately, the growth in the participation of women's Rugby union has not been matched with scientific evidence-based literature that seeks to improve the performance of this population of players. Therefore, due to the unavailability of match-play during the COVID-19 outbreak, this study aimed to quantify the physical and physiological demands of training sessions of amateur women's Rugby union players from the Sarah Baartman District, South Africa using Global Positioning System (GPS). The training' data collected was compared to previous literature, including studies that also focused on match-play. Furthermore, players were categorized into forwards and backs, allowing for the comparison between the two playing categories. An exploratory, descriptive, observational, and comparative research design was used for the current study. The physical and physiological demands of eighteen women Rugby union players (eight forwards and ten backs) aged between 18 "“ 36 years old were assessed during training (for a total of nine sessions). To inform the participants' characteristics, the players' demographic, and anthropometric characteristics (age, stature, and body mass) were obtained. Using GPS and Zephyr technology the players' training physical (time spent in speed zones, maximum speed, total distance travelled, number of impacts in the various impact zones) and physiological (heart rate) demands were explored. Statistical analysis methods including descriptive, independent t-test, one-way and two-way ANOVA tests were employed to analyse the data and evaluate the differences between forwards and backs. The mean age and stature for all players was 25,44Â±5,6 years and 1,60Â±0,06 m respectively, with no significant differences found between backs and forwards. With regards to body mass, forwards weighed 82,0Â±9,4 kg while backs weighed significantly lighter at 58,0Â±5,8 kg. Significant differences (p < 0,05) were found for all players in the time spent in speed zones and the number of impacts in impact zones. When all forwards' and backs' physical and physiological demands were compared the results showed no significant differences. The average time spent in all six speed zones combined was 11,41 and 11,62 mins for forwards and backs, respectively. The maximum speeds reached by forwards (21,35Â±5,72 km/h) and backs (22,85Â±3,88 km/h) were similar. All players combined travelled an average total distance of 2,14Â±0,76 km. The total number of impacts in all six impact zones, totalled 116 impacts for forwards and 97 for backs. Heart rate responses recorded for forwards and backs were 139Â±15 bpm and 134Â±13 bpm. Based on the findings of this study, the training intensity of amateur women's Rugby union was lower than the demands experienced in the training and match-play of previous research. It was also observed that there was no specificity with regards to the training programs allocated between forwards and backs of this study. Further research on amateur women's Rugby union is required to characterise training and match-play demands of these players.
Keywords: Rugby Union football Physiological aspects; Women Rugby Union football players -- South Africa -- Eastern Cape; Global Positioning System; Rugby football injuries; Amateur sports; Physical fitness and technology